PENGARUH PENGGUNAAN ABU BATU DAN MORTAR INSTAN TERHADAP KUAT TEKAN BETON - Agamuddin, Agri Americo; Nugroho, Fajar (Ensiklopedia Education Review, 2023)
Stone ash is one of the results of the crushed stone production process with a stone crusher which produces small and fine grains. This experimental research was carried out by adding stone ash and instant mortar (MU type 400) at 5%, 7,5% and 10% to normal concrete with a design compressive strength fc' 25 MPa. The research results show that the addition of 10% stone ash and instant mortar to the concrete mixture can reduce the slump value. This shows that stone ash and instant mortar with an addition percentage of 10% have a high water absorption capacity.  Stone ash and instant mortar function as additives for fine aggregate and Portland cement in concrete to improve the quality of the concrete. The results of concrete compressive strength testing show that the addition of stone ash and instant mortar with an addition percentage of 10%, has the highest compressive strength value of 31,26 MPa, an increase of 4,98% compared to concrete without the addition of stone ash and instant mortar. Keywords: Concrete, compressive strength, stone ash, instant mortar